Contemporary European theatre directors - Delgado, Maria M.; Rebellato, Dan, 1968- (Routledge, 2020)
"This expanded second edition of Contemporary European Theatre Directors is an ambitious and unprecedented overview of many of the key directors working in European theatre over the past thirty years. This book is a vivid account of the vast range of work undertaken in European theatre during the last three decades, situated lucidly in its artistic, cultural, and political context. Each chapter discusses a particular director, showing the influences on their work, how it has developed over time, its reception, and the complex relation it has with its social and cultural context. The volume includes directors living and working in Italy, Germany, France, Spain, Poland, Russia, Romania, the UK, Belgium, Switzerland, and the Netherlands, offering an all-encompassing, global approach across the directing field. Now revised and updated, Contemporary European Theatre Directors is an ideal text for both undergraduate and postgraduate directing students, as well as those researching contemporary theatre practices, providing a detailed guide to the generation of directors whose careers were forged and tempered in the changing Europe since the end of the Cold War"--